Предмет: Алгебра,
автор: Аноним
Упростите выражение: −9a(8a2+2)(3a2+7)
Ответы
Автор ответа:
0
Ответ:
раскрывает фонтанчиком
Объяснение:
(-72а3-18а)(3а2+7)=-216а5-504а3-54а3-126а=-216а5-588а3-126а
Автор ответа:
0
Ответ:
Объяснение:
−9a(8a²+2)(3a²+7)=(-72а³-18а)(3a²+7)=
-216а⁵-504а³-54а³-126а=-216а⁵-558а³-126а
Похожие вопросы
Предмет: Английский язык,
автор: Kagura001
Предмет: Русский язык,
автор: vasilisabragin
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Геометрия,
автор: nazar16062004
Предмет: Математика,
автор: Nahazh228